Sanatório Getúlio Vargas: medicina e relações sociais no combate da tuberculose no Espírito Santo (1942-1967) - Rios, Maria Zilma (2009)
The present work – SANATORIUM GETÚLIO VARGAS: medicine and social relations in the combat of the tuberculosis in Espirito Santo State (1942-1967) -, has the purpose of presenting a study on the trajectory of the Sanatorium Getúlio Vargas and its importance in the combat of the tuberculosis for the State of Espirito Santo. According to data collected through written records, interviews and iconographic sources which were compared to the bibliography about the history of the health in Brazil, it was possible to develop a qualitative research which main object is the Sanatorium Getúlio Vargas itself. The research provided the knowledge of the daily routine of patients with tuberculosis and health professionals who were responsible for this area between the years of 1942 and 1967 (period of the construction and functioning of the Sanatorium). Through the establishment of social relations inside the physical space where the hospital net of combat of the tuberculosis in Vitória was established, a senatorial and self-sufficient society was formed in several aspects and, in a certain way, isolated from the rest of the society. From this identification on, the work was developed and the target was the tuberculosis and its combat, being indispensable the analysis of public politics toward the health and intensified with the arrival of the 1930 decade.